Digital Reconstruction: A Critical Examination of the History and Adaptation of Ku Klux Klan Websites - Kingdon, Ashton (Journal of interpersonal violence, 2024)
In response to the data revolution, academic research and media attention have increasingly focused on the technological adaptation and innovation displayed by the far right. The greatest attention is paid to social media and how groups and organizations are utilizing technological advancement and growth in virtual networks to increase recruitment and advance radicalization on a global scale. As with most social and political endeavors, certain technologies are in vogue and thus draw the attention of users and regulators and service providers. This creates a technological blind spot within which extremist groups frequently operate older and less well regarded technologies without the oversight that one might expect. This article examines the less well-studied traditional and official websites of the Ku Klux Klan, the most established and iconic of American far-right organizations. By incorporating non-participant observation of online spaces and thematic analysis, this research analyzes the evolution of 26 websites, from their emergence in the early 1990s to the present day. We examine the ways in which traditional printed communications and other ephemera have progressed with advances in technology, focusing on the following central elements of Klan political activism and community formation: Klan identity, organizational history, aims and objectives; technology and outreach, including online merchandise and event organization; and the constructions of whiteness and racism. The results add value and insight to comparable work by offering a unique historical insight into the ways in which the Klan have developed and made use of Web 1.0, Web 2.0, and Web3 technologies.